Electrocardiographic Ccharacteristics of metastatic cardiac tumors presenting with ST-segment elevation - KEPEZ, ALPER (CHURCHILL LIVINGSTONE INC MEDICAL PUBLISHERS, 2020)
Introduction: ST segment elevation (STE) in the standard 12-lead surface electrocardiography (ECG) is a well-known finding in patients with metastatic cardiac tumors. It is important to identify the specific characteristics of STE among those patients to prevent unnecessary aggressive treatments. In the present study, we aimed to demonstrate the ECG characteristics of patients with metastatic cardiac tumors who has STE. Material and methods: Medical literature was searched from Pubmed database with key words metastatic cardiac tumors or cardiac tumors and ST segment elevation or ST elevation. In addition, remaining articles were explored using the references of case reportswhichwere obtained during former screening (snowball procedure). Results: Thirty six of 46 case reports were included and ECG characteristics of each case were evaluated. Convex-shaped STE was observed in all patients and it showed a specific coronary territory in 35 of 36 patients (97.2%). Pathologic Q wave and/or loss of R wave progression were observed in only one patient. T wave inversion following STE was detected in 34 patients (94.4%). STE evolution was absent in 32 of 36 patients while the information regarding STE evolution were not provided in the remaining cases. Conclusion: STE due to tumor invasion has certain characteristics which could help clinicians in the differential diagnosis. (c) 2019 Elsevier Inc. All rights reserved.
Keywords: Cardiac metastasis; ST segment elevation; Electrocardiography; ACUTE MYOCARDIAL-INFARCTION; CANCER MIMICKING; VENTRICULAR METASTASIS; INFILTRATION; CARCINOMA; HEART; SECONDARY; INVASION